The strategy to control the outbreak of an emerging respiratory infectious disease in a simulated Chinese megacity - Zhiqun Lei; Ziwei Shi; Jiao Huang; Xiaolong Yan; Jiayao Luo; Meng Xu; Qiuyue Wang; Rui Wang; Qi Wang; Qu Cheng; Sheng Wei (Heliyon)
Abstracts: Objectives: The emergence of respiratory infectious diseases (ERID) poses a significant threat to global public health. However, effectively managing ERID outbreaks in large cities remains a challenge. Methods: An age-structured Susceptible-Exposed-Infectious-Removed (SEIR) model was developed to predict the effectiveness of non-pharmaceutical interventions (NPIs) in controlling ERID outbreaks. Four ERID outbreak scenarios were created based on varying levels of infectivity and pathogenicity. Based on the World Health Organization's (WHO) categorization for responding to the influenza pandemic, the combinations of NPIs were classified into five levels: base, any, moderate, high, and extraordinary levels (from mild to severe). The simulated progression of ERID outbreaks in a megacity were compared across different levels of NPI. Results: Our findings indicate that the response strategies should be formulated based on the epidemiological characteristics of ERID. In the low transmission scenarios, the mandatory NPIs were unnecessary to control ERID outbreaks regardless of their pathogenicity. However, even with low pathogenicity, severe NPIs are required to control the spread of ERID and minimize harm to the public in high transmission scenarios. Conclusion: The NPIs for the EIRD outbreak in a city should be tailored to the epidemiological characteristics to control its impact and protect public health.